Proactive nursing interventions on side effects during the treatment of acute promyelocytic leukemia with arsenic trioxide: A mixed-methods study in Piacenza - Guasconi, Massimo; Maserati, Martina; Fargione, Nadia; Quitadamo, Vincenzo Matteo; Casella, Giovanna (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Acute promyelocytic leukaemia (APL) accounts for about 10% of acute myeloblastic leukaemias in adults and has become the most potentially curable subtype.Randomised trials have demonstrated the efficacy and safety of the arsenic trioxide and all-trans retinoic acid (ATO/ATRA) protocol without chemotherapy as first-line therapies in patients with low-risk APL. Despite the progress achieved in the treatment of APL, complications often occur therefore rapid intervention is required.No articles can be found in the literature on the centrality of the nurse in the management of patients in treatment with ATO, but daily experience shows that nursing care also plays a key role in the success of therapy by preventing adverse events. The aim of the study is to find out whether and which proactive nursing interventions can reduce the consequences of major drug side effects on the patient, improve compliance and the patient's course of treatment.Methods: This study was carried out through a retrospective survey of medical records combined with qualitative 14 semi-structured interviews with operators and patients at the U.O. Haematology in-patient unit.Results: Considering that the patients in this study were hospitalized for an average of 39 days, out of a total of a mean number of 542 interventions carried out during a single 39-day hospitalization, the frequency of autonomous interventions was 395 (73%) compared to 147 (27%) of collaborative interventions.Conclusions: Although the results obtained underline the centrality of the nurse and the proactive interventions, the narrowness of the sample makes it necessary to undertake further investigations.